The primary carer's experience of caring for a person with a mental disorder in the Western Australian community: a grounded theory study - Wynaden, Dianne Gaye (Curtin University, 2002)
One in five Australians has a mental disorder and it is estimated that one in four families have a member who has a mental disorder. Since the 1960s there has been an 80 percent decrease in Australian institution-based mental health care. The majority of people who have a mental disorder are now treated in their local community and many of them live with their families. The change in the delivery of mental health care has seen the family emerge as one of the most important supports to their ill family member. While the changes in the delivery of mental health care have been based on human rights concerns, changes in mental health legislature, and economic factors, the multi-dimensional experience of being a primary carer of a person with a mental disorder remains relatively unexplored. The need for empirical evidence on the primary carer's experience is noted in both the scientific literature and from carers themselves and the principal aim of conducting this research was to address the identified need. This qualitative study, using grounded theory methodology, presents the findings of interviews with 27 primary carers and memos documented throughout the study. In addition, existing literature of relevance to the findings of this study is presented. A substantive theory of seeking balance to overcome being consumed is presented in this thesis. Using the grounded theory method the constant comparative analysis of data revealed that the basic social psychological problem shared by all participants was the experience of "being consumed". The problem of being consumed consisted of two stages: "disruption of established lifestyle" and a "sustained threat to self-equilibrium". Six conditions were identified as influencing participants' experience of being consumed.In order to address the problem of being consumed, participants engaged in a basic social psychological process of "seeking balance". When participants were engaged in this process they moved from a state of being consumed to one whereby they established and consolidated a balanced life perspective that incorporated their caregiving role. The process of seeking balance consisted of three phases: "utilising personal strategies to reduce the problem of being consumed', "restoring self- identity", and "reaching out to make a difference". In addition, data analysis identified the presence of a three phase sub-process entitled "trying to make sense of what was happening". Phases one of the core and sub- processes occurred primarily in the period prior to the time when a psychiatric diagnosis was made on the affected family member. Participants became engaged in the remaining two phases of the core and sub-processes when they became aware that their affected family member had a mental disorder. At the time of being interviewed for this study some participants were not yet engaged in the final phase of the process of seeking balance. Participants' experience of seeking balance was not related to the length of their caregiving experience but rather to their experience of seeking balance and the conditions influencing that process. Four conditions were identified as influencing participants' experience of seeking balance.This thesis presents the substantive theory of seeking balance to overcome being consumed. While the findings support existing scientific literature, the substantive theory also presents a new insight on caring from the primary carer's perspective. In particular, the findings challenge health professionals to actively pursue strategies to reduce carers' experience of being consumed. The findings of this study have implications for service provision and clinical practice, policy and planning, research, education, the general population, mental health consumers, and carers.